EXPRESSION OF TOLL PROTEIN GENE IN LITOPENAEUS VANNAMEI (PACIFIC WHITE SHRIMP) EXPERIMENTALLY INDUCED WITH VIBRIO ALGINOLYTICUS - SOWMYA. M.V; UMA. A; REBECCA. G (International Journal of Pharma and Bio Sciences, 2013)
Toll proteins are components of innate immune system known to be involved in the recognition of pathogen associated molecular patterns (PAMPs), the conserved motifs of the pathogens and in eliciting the immune response. This study was carried out with an objective to identify the expression of Toll protein gene in Litopenaeus vannamei and to compare its expression profiles in healthy and experimentally induced status. L.vannamei was experimentally induced by exposure to Vibrio alginolyticus at a concentration of 9×1012 colony forming units/ml (CFU ml-1). Tissues of various organs viz., muscle, gut, gills, heart, nerve and pleopods of L.vannamei that were healthy and experimentally exposed with V.alginolyticus were used to study the toll protein gene expression profile by Reverse transcriptase Polymerase chain reaction (RT- PCR). Basal expression of toll protein gene at various levels was observed in muscle, gut, gills, heart, nerve and pleopods of healthy L. vannamei. Comparatively higher levels of toll protein gene expression were observed in the tissues of L. vannamei that were experimentally exposed with V.alginolyticus, the highest induced expression level was recorded in the nerve tissue.